Las bromeliaceae del Estado de Morelos, México - González Rocha, Edith (Universidad Autónoma Metropolitana, 2014)
The Bromeliaceae family comprises 58 genera and 3,348 species distributed in tropical and subtropical regions of Central and South America. In Mexico, the family is represented by four subfamilies: Bromelioideae, Hechtioideae, Pitcairnioideae and Tillandsioideae with 19 genera and ca. 400 species. A taxonomic treatment for Bromeliaceae in Morelos state is presented, including keys and descriptions for the genera and species. Each taxón includes: synonymy, voucher herbarium specimens for each municipality as well as municipality distribution, elevation, vegetation type, phenology phorophytes, maps of current and potential distribution and photographs of the plants. We have found six genera and 35 species, representing 8.75% of the 400 taxa reported for Mexico. The genera with most species are Tillandsia (20), Hechtia (5), and Pitcairnia (4); whereas Catopsis and Viridantha have two taxa respectively, and Bromelia has a single species. Hechtia chichinautzensis, H. montisfrigidi, Pitcairnia sp. 1, P. sp. 2 and Tillandsia sp. 1 and T. sp. 2 are endemic to Morelos. Fort he first time we have recorded in Morelos four taxa ,two ofthe genus Catopsis with C. nutans and C. paniculata, and two of Tillandsia: T. juncea, the first three widespread in the country, and T. langlasseana only known from Guerrero, Estado de México and Michoacán. It is worth mentioning thath we have collected plant material of six new species not described until now, belonging to Hechtia (2), Pitcairnia (2) and Tillandsia (2) genera. Morelos has 33 municipalities, of which Tepoztlán hosts 60% of the recorded species, followed by Cuernavaca, Puente Ixtla and Tlayacapan that concentrates between 31 and 37%. Among the eight vegetation types of Morelos, the richest in bromeliads is the tropical deciduous forest with 19 taxa, followed by oak forests with 17 taxa. Three species inhabit in specific locations of cliffs or rock walls in cloud and oak forests. Twenty two species are apiphytic and 42 taxa of phorophytes was recorded, the species of Quercus has 15epiphytic bromeliads and the Bursera species has 10.; Las Bromeliaceae agrupan 58 géneros y 3,348 especies distribuidas en las regiones tropicales y subtropicales de Centro y Sudamérica. En México, la familia está representada por cuatro subfamilias: Bromelioidae, Hechtioideae, Pitcairnioideae y Tillandsioideae, con 19 géneros y casi 400 especies. Se presenta el tratamiento taxonómico de la familia para el estado de Morelos, incluyendo claves y descripciones para los géneros y las especies. Para cada taxón se incluye sinonimia, distribución municipal, ejemplares examinados por municipio, altitud, tipo de vegetación, fenología, forófitos asociados, mapas de distribución y fotografías de las plantas. Se reportan para el estado 6 géneros y 35 especies, cifra que representa 8.75% de los 400 taxa reportados para el país. Los géneros más ricos en especies son Tillandsia (20), Hechtia (5) y Pitcairnia (4) mientras que Catopsis y Viridantha cuentan con dos cada uno y Bropmelia tiene una sola. En cuanto al endemismo, Hechtia chichinautzensis, H. montis-frigidi, Pitcairnia sp. 1, P. sp. 2, Tillandsia sp. 1 y T. sp. 2, restingen su distribución a Morelos. Se registra por primera vez para la entidad al género Catopsis, con C. nutans y C. paniculata, así como Tillandsia juncea, los tres taxa de amplia distribución en el país, así como a T. langlasseana, especia conocida solo en Guerrero, Estado de México y Michoacán. Cabe mencionar además que se ha recolectado material de sies especies no descritas para la ciencia pertenecientes a los géneros Hechita (2), Pitairnia (2) y Tillandsia (2). De los 33 municipios que conforman al estado, Tepoztlán alberga el 60% de las especies registradas, seguido por Cuernavaca, Puente de Ixtla y Tlayacapan que concentran entre 31 y 37%. De los ocho tipos de vegetación que prosperan en Morelos, el más rico en bromeliáceas es el bosque tropical caducifolio con 19 taxa, seguido del bosque de Quercus con 17 y tres especies crecen en localidades puntuales sobre riscos o paredes rocosas en bosque mesófilo de montaña y en bosque de coníferas o Quercus. Para las 22 especies de bromelias epífitas, se registran 42 taxa de forófitos, de los cuales los correspondientes al género Quercus albergan 15 y los de Bursera 10.